Narasi dari Sang Rival - Wijaya, Daya Negri (Jurnal Sejarah, 2020)
This paper attempts to narrate Achinese invasions of Malacca according to Portuguese sources. The use of various perspectives should be devised in order to re-narrate a specific historical episode. In the context of the Achinese invasion of Portuguese Malacca, Indonesian historians merely depend on the availability of the local and Dutch sources. The rich information, meanwhile, is recorded in bulk of Portuguese manuscripts. The local sources are silent related to all Achinese failures. The quiet locals should be considered in their spirit of the age that the Achinese chronicles are written to praise the glorious king and the success of the royal expansion. Therefore, the Achinese chronicles are in brief to mention the invasion of Malacca. The use of Portuguese sources should be promoted, but the existence of other sources remains considered. If the Portuguese sources could direct the historians to narrate the historical episode in detail, therefore, the other sources could be a corresponding source and a reference to verify the related data.